Administrative Cost Inefficiency of Local Tax Collection: Comparing Cities and Regencies in Supporting SDG 16 - Jalu Aji Prakoso; Arif Rahman Saleh; Suci Nasehati Sunaningsih; Khresna Bayu Sangka (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To measure the technical efficiency of local tax collection and identify the factors affecting the technical inefficiency of tax collection administrative costs in regency and city governments in Central Java Province. Method: Employing a quantitative approach using cross-sectional data from 35 regencies and cities in Central Java Province in 2019. Tax collection administrative costs are measured using the expenditure approach and analyzed using Stochastic Frontier Analysis (SFA) with Maximum Likelihood Estimation (MLE). Results: Local Own-Source Revenue (PAD) has a positive and significant effect on tax collection administrative costs. Gross Regional Domestic Product (GRDP) has a negative and significant effect, indicating that stronger economic activity improves tax collection efficiency. Population size significantly affects administrative costs, while the administrative status dummy variable reveals efficiency differences between regency and city governments. In addition, the size of the administrative area has a significant negative effect on technical inefficiency. The average technical efficiency of local tax collection reaches 87.34%, indicating that there is still room for efficiency improvement. Novelty: Contributing to the local public finance and sustainable governance literature by applying Stochastic Frontier Analysis (SFA) to evaluate tax collection administrative efficiency and comparing efficiency performance between regency and city governments in Central Java. The findings provide empirical evidence on how efficient local tax administration can support SDG 16 through the strengthening of effective and accountable public institutions under fiscal decentralization.